The influence of high worry on static and dynamic insular functional connectivity - Zhang, Youxue; Cai, Xueli; Duan, Mingjun; He, Hui (Frontiers in Neuroscience, 2023)
Worry is a form of repetitive negative thought. High worry-proneness is one risk factor leading to anxiety disorder. Several types of research indicated that anxiety disorder was highly associated with disrupted interoception. The insula is consistently considered as key role of interoception. However, the relationship between worry and interoception network is poorly investigated in worry-proneness individuals. Thus, it is essential to identify the neural characteristic of high worry-proneness subjects. 32 high worry-proneness subjects (HWP) and 25 low worry-proneness subjects (LWP) recruited and underwent Magnetic Resonance Imaging scanning. Six subregions of insula were chosen as regions of interest. Then, seed-based static and dynamic functional connectivity were calculated. Increased static functional connectivity was observed between the ventral anterior insula and inferior parietal lobule in HWP compared to LWP. Decreased static functional connectivity was found between the left ventral anterior insula and the pregenual anterior cingulate cortex. Decreased dynamic functional connectivity was also showed between the right posterior insula and the inferior parietal lobule in HWP. Moreover, a post hoc test exploring the effect of changed function within insular region, confirmed that a significant positive relationship between static functional connectivity (ventral anterior insula-inferior parietal lobule) and dynamic functional connectivity (posterior insula-inferior parietal lobule) in LWP, but not in HWP. Our results might suggest that deficient insular function may be an essential factor that related with high worry in healthy subjects.